Faut-il privilégier l’emploi de la langue maternelle chez les adeptes de la traduction ? - Kasperska, Iwona (AMU Press, 2011)
The paper describes two main methods of teaching text translation, applied in courses of literary and specialized texts translation for a general public, and in a specialized course of translation for MA advanced students. In both methods the use of Polish language as a mother tongue is considered legitimate not only as a language of translation but also as a main vehicle of communication in the process of acquiring translation skills. This role of the mother tongue is extremely important in defining the translation brief and in the evaluation of target texts. The article provides several examples in order to illustrate and justify this thesis.
Is it necessary for translation didactics to let students use their mother tongue?